Determination of Necessary and Sufficient Operational Conditions of The Sleeve-Type Bearings in Autonomous Power Plants of Ormat Type Under Conditions of Siberia and the Far East; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Vysokomornaya O. V. Olga Valeryevna; Vysokomorny (Vysokomorniy) V. S. Vladimir Sergeevich; Beck A. S. Alexander; Kosintsev A. G. Andrey; Panin V. F. Vladimir Filippovich (2016, 2016)
Title screen